Phenotypic expansion of TBX4 mutations to include acinar dysplasia of the lungs. Issue 9 (4th July 2016) - Szafranski, Przemyslaw; Coban‐Akdemir, Zeynep H.; Rupps, Rosemarie; Grazioli, Serge; Wensley, David; Jhangiani, Shalini N.; Popek, Edwina; Lee, Anna F.; Lupski, James R.; Boerkoel, Cornelius F.; Stankiewicz, Paweł
Abstract : Mutations in the T‐box transcription factor TBX4 gene have been reported in patients with Ischiocoxopodopatellar syndrome (MIM# 147891) and childhood‐onset pulmonary arterial hypertension. Whole exome sequencing of DNA from a 1 day old deceased newborn, with severe diffuse developmental lung disorder exhibiting features of acinar dysplasia, and her unaffected parents identified a de novo TBX4 missense mutation p.E86Q (c.256G>C) in the DNA‐binding T‐box domain. We propose phenotypic expansion of the TBX4 ‐related clinical disease spectrum to include acinar dysplasia of the lungs. The reported mutation is the first identified genetic variant causative for acinar dysplasia. © 2016 Wiley Periodicals, Inc.